1993
DOI: 10.5741/gems.29.3.191
|View full text |Cite
|
Sign up to set email alerts
|

Two Near-Colorless General Electric Type-IIa Synthetic Diamond Crystals

Abstract: Of all the gem-quality synthetic diamonds that could potentially enter the jewelry trade, faceted near-colorless synthetic diamonds are the greatest concern. Not only do near-colorless diamonds represent the vast majority of stones in the jewelry industry, but the techniques the jeweler typically uses to quality grade these stones are different from those needed to separate natural from synthetic diamonds. Yet relatively few near-colorless gemquality synthetic diamonds have been made available for gemological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The strong, persistent phosphorescence observed for colorless to near-colorless HPHT Type IIa and IIb diamonds is also particularly useful for their detection due to the rarity of phosphorescence in similarly colored natural diamonds (Fig. 35b) (Crowningshield 1971;Koivula and Fryer 1984;Rooney et al 1993;Shigley et al 1993bShigley et al , 1997D'Haenens-Johansson et al 2014. The phosphorescence, associated with boron (Watanabe et al 1997), indicates the presence of this element even in nominally Type IIa HPHT diamonds.…”
Section: Luminescence Behavior Tablementioning
confidence: 99%
See 2 more Smart Citations
“…The strong, persistent phosphorescence observed for colorless to near-colorless HPHT Type IIa and IIb diamonds is also particularly useful for their detection due to the rarity of phosphorescence in similarly colored natural diamonds (Fig. 35b) (Crowningshield 1971;Koivula and Fryer 1984;Rooney et al 1993;Shigley et al 1993bShigley et al , 1997D'Haenens-Johansson et al 2014. The phosphorescence, associated with boron (Watanabe et al 1997), indicates the presence of this element even in nominally Type IIa HPHT diamonds.…”
Section: Luminescence Behavior Tablementioning
confidence: 99%
“…Consequently, they have low internal strain levels and only show extremely weak (black, gray or blue interference colors)-or more typically no-strain birefringence patterns, except adjacent to inclusions and cracks (Fig. 34) (Crowningshield 1971;Lang et al 1991;Fritsch and Shigley 1993;Rooney et al 1993;Shigley et al 1993b;D'Haenens-Johansson 2014. Natural diamonds commonly show mottled, banded, radial, or tatami (cross-hatched) birefringence patterns originating from the presence of defects, inclusions, and deformation events from their growth and mantle residency history (Tolansky 1966;Lang 1967;Kane 1980;Sumiya et al 1997;Howell 2012).…”
Section: Strain Birefringence Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear, however, that the economic production of near-colorless synthetic diamonds in a size and quality suitable for jewelry was at least one of the goals explored by diamond synthesizers during the last decade (Rooney et al, 1993;Shigley et al, 1997). By 1990, General Electric had demonstrated that they could grow near-colorless type IIa diamonds exceeding 1 ct using a transition-metal flux to prevent the incorporation of nitrogen and boron impurities (Shigley et al, 1993b). In addition, they experimentally synthesized large (up to 3 ct) colorless carbon-13 diamonds, which-theoretically-could be harder than carbon-12 based diamonds .…”
Section: Synthetic Diamondmentioning
confidence: 99%
“…Throughout the 1990s, HPHT diamond synthesis employed a variety of large presses (see, e.g., figure 5). These included a belt-type apparatus (a piston/cylinder press with a special, strengthened central cylinder); multiple-anvil presses with tetrahedral, octahedral (Koivula and Kammerling, 1991b), or cubic symmetry; and split-sphere presses (sometimes called BARS for the Russian initials: see, e.g., Koivula et al, 1992d;Shigley et al, 1993b). Most HPHT synthetic diamonds are grown in a nickel-iron flux (see, e.g., Burns et al, 1999;Choudhary and Bellare, 2000); high-quality synthetic diamonds, with fewer defects than natural diamonds, can be grown using a temperature gradient in the HPHT cell (Pal'yanov et al, 1998).…”
Section: Colored Stone Synthesismentioning
confidence: 99%